Dual Role of Interleukin-10 in Murine NZB/W F1 Lupus - Anaïs Amend (International Journal of Molecular Sciences, 2021)
As a key anti-inflammatory cytokine, IL-10 is crucial in preventing inflammatory and autoimmune diseases. However, in human and murine lupus, its role remains controversial. Our aim was to understand regulation and immunologic effects of IL-10 on different immune functions in the setting of lupus. This was explored in lupus-prone NZB/W F1 mice in vitro and vivo to understand IL-10 effects on individual immune cells as well as in the complex in vivo setting. We found pleiotropic IL-10 expression that largely increased with progressing lupus, while IL-10 receptor (IL-10R) levels remained relatively stable. In vitro experiments revealed pro- and anti-inflammatory IL-10 effects. Particularly, IL-10 decreased pro-inflammatory cytokines and slowed B cell proliferation, thereby triggering plasma cell differentiation. The frequent co-expression of ICOS, IL-21 and cMAF suggests that IL-10-producing CD4 T cells are important B cell helpers in this context. In vitro and in vivo effects of IL-10 were not fully concordant. In vivo IL-10R blockade slightly accelerated clinical lupus manifestations and immune dysregulation. Altogether, our side-by-side in vitro and in vivo comparison of the influence of IL-10 on different aspects of immunity shows that IL-10 has dual effects. Our results further reveal that the overall outcome may depend on the interplay of different factors such as target cell, inflammatory and stimulatory microenvironment, disease model and state. A comprehensive understanding of such influences is important to exploit IL-10 as a therapeutic target.